Proinflammatory cytokines VEGFA, IL-6, IL-8 as markers of hepatotoxicity after COVID-19 - M. A. Urevskii; L. V. Ilmukhina; Ya. E. Saranskaya; A. A. Lapshin; R. R. Gafurova (Медицинская иммунология, 2023)
The mechanism of hepatocellular liver damage after COVID-19 is a multifactorial process. The most widely discussed causes are cytolytic liver damage due to the inflammatory response after COVID-19, drug-induced hepatotoxicity and direct cytotoxic effect of the virus. There are observations that SARSCoV-2 infection causes hepatitis B virus reactivation, but little has been described about the interaction between hepatitis C virus and SARS-CoV-2. The course of coronavirus infection is associated with marked expression of proinflammatory cytokines, participants in the multisystem inflammatory response, IL-1β, IL-6, IL-8, IL-18, MCP-1, TNFα, which contribute significantly to the observed early and late liver function impairment. The aim of the study was to evaluate the role of proinflammatory cytokines (VEGFA, IL-8, IL-6, MCP-1, TNFα, IL-18) as additional markers of hepatotoxicity after COVID-19. The study was performed between March and August 2022. Patients were divided into 2 groups: Group 1 – with increased aminotransferases against the background of treatment from COVID-19 and/or in the following 3-6 months after the disease without viral liver damage (n = 42), Group 2 – patients with co-infection (chronic viral hepatitis C (HCV) and COVID-19 (n = 26). The levels of cytokines – VEGF-A, IL-6, IL-8, MCP-1, IL-18, TNFα in blood serum were estimated by enzyme immunoassay method. Statistical analysis was performed using StatTech v. 3.1.4. The results of the study revealed a comparable increase in the level of transaminases and C-reactive protein in both groups, significantly different from the reference values. Direct correlations of moderate strength (linear Spearman correlation) were found between the following cytokines: TNFα-MCP-1 (R = 0.559; p = 0.001), TNFα-VEGFA (R = 0.400; p = 0.002), TNFα-IL-6 (R = 0.503; p = 0.001). We diagnosed a significant increase in serum VEGFA levels in group 1 patients (hepatotoxicity after COVID-19) (Me (Q0.25-Q0.75): 522 (250 to 1002), p = 0.001) and in group 2 patients (HCV + COVID-19) (Me 1196, Q0.25-Q0.75: (73 to 432). Similar trend with the level of IL-6, IL-8, exceeding the values of cytokines in healthy donors and significantly higher than in group 2 patients. Identified correlations between inflammatory cytokines prove unidirectional changes in the functioning of the regulatory network controlling immune virus-induced reactions.